2008
DOI: 10.1002/pbc.21612
|View full text |Cite|
|
Sign up to set email alerts
|

MRI abnormalities of the brain in one‐year‐old children with sickle cell anemia

Abstract: Silent brain infarcts occur in a small but significant number of infants with SCA as early as a year of age. This finding indicates a need for thorough evaluation of the CNS very early in life in children with SCA in order to develop timely intervention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 23 publications
4
68
1
Order By: Relevance
“…31 The lower hemoglobin levels may explain in part why SCIs have been detected in an infant as young as 7 months 32 and in several infants younger than 15 months. 33 The majority of SCIs occur in children younger than 6 years, 4 as the hemoglobin levels decline continuously until levels reach steady state. 31 In addition to our findings that low hemoglobin levels are associated with SCI, two singlecenter studies of children with SCA have demonstrated similar findings.…”
Section: Org Frommentioning
confidence: 99%
“…31 The lower hemoglobin levels may explain in part why SCIs have been detected in an infant as young as 7 months 32 and in several infants younger than 15 months. 33 The majority of SCIs occur in children younger than 6 years, 4 as the hemoglobin levels decline continuously until levels reach steady state. 31 In addition to our findings that low hemoglobin levels are associated with SCI, two singlecenter studies of children with SCA have demonstrated similar findings.…”
Section: Org Frommentioning
confidence: 99%
“…The severity of anemia, a history of recurrent acute chest syndrome, obesity, and elevated blood pressure are all considered independent risk factors for the development of stroke (Akingbola et al, 2014;Ohene-Frempong et al, 1998;Wang et al, 2008). Other risk factors include prior transient ischemic attack, low steady-state hemoglobin levels, hypertension, and high leukocyte counts (Ohene-Frempong et al, 1998).…”
Section: Stroke In Scdmentioning
confidence: 99%
“…SCI have been reported in very young children; 4/39 children (10%) with SCA and no history of stroke between 7 and 48 months of age had SCI [9]; 3/23 children (13%) at an average age of 13.7 months had SCI [10]; and 18/65 children (27.7%) with SCA who were asymptomatic had SCI [31]. A French study showed incidence of SCI as 28.2% by 8 years and 37.4% by 14 years [66].…”
Section: Progression Of Scimentioning
confidence: 99%
“…Silent cerebral infarction (SCI) is diagnosed only using magnetic resonance imaging (MRI) in patients with no focal neurological deficit, but is associated with cognitive difficulties [8] that families often report. SCI can develop very early in life, with rates between 11 and 15% in children less than 2 years [9][10][11] and progressive accrual throughout childhood and adolescence [11,12] and into adulthood.…”
Section: Introductionmentioning
confidence: 99%